Education through multimedia: advantages and limitations / M. V. Ramachandra - Ramachandra, M.V. (Faculty of Communication and Media Studies (FCMS), 2004)
Multimedia developments continuously change the traditional education methods. The convergence in multimedia is increasing the learning capacity and reaching power. The various media like print, audio, video, computer and internet-based media are very important in today's education world. A properly designed syllabus through multimedia will give more impact and better results. But the individual medium has its own advantages and limitations. This paper discusses the advantages and limitations of education through multimedia, which will give the solutions to rectify the problems, while creating and setting-up multimedia lessons and the syllabus.